2017
DOI: 10.1128/genomea.01706-16
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Porcine Deltacoronavirus Strains DH1/2016 and DH2/2016 Isolated in South Korea

Abstract: Two porcine deltacoronavirus (PDCoV) strains, named DH1/2016 and DH2/2016, were isolated from feces of piglets which had severe watery diarrhea symptoms. A comparison of the complete genome sequences suggested that the DH1/2016 and DH2/2016 strains are highly homologous to each other and to PDCoVs isolated in early 2014 from the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Acute cases of PDCoV infection exhibit watery diarrhea in sows and nursing piglets, resulting in severe gastrointestinal disease which may have a lethal outcome [4][5][6]. PDCoV poses a major threat to the swine industry, and is currently epidemic in several countries; first reported in Hong Kong in 2012 [7], it has since been found in the United States [8][9][10], Canada [11], South Korea [12][13][14][15], mainland China [16][17][18][19], Thailand [20][21][22] and Vietnam [23]. Importantly, porcine aminopeptidase N (pAPN) has been reported to serve as a functional receptor for PDCoV in two recent studies [24,25], and the virus may engage APN from diverse species to facilitate its interspecies transmission [25].…”
Section: Introductionmentioning
confidence: 99%
“…Acute cases of PDCoV infection exhibit watery diarrhea in sows and nursing piglets, resulting in severe gastrointestinal disease which may have a lethal outcome [4][5][6]. PDCoV poses a major threat to the swine industry, and is currently epidemic in several countries; first reported in Hong Kong in 2012 [7], it has since been found in the United States [8][9][10], Canada [11], South Korea [12][13][14][15], mainland China [16][17][18][19], Thailand [20][21][22] and Vietnam [23]. Importantly, porcine aminopeptidase N (pAPN) has been reported to serve as a functional receptor for PDCoV in two recent studies [24,25], and the virus may engage APN from diverse species to facilitate its interspecies transmission [25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a porcine delta CoV (PDCoV) HKU15, was identified in Hong Kong in 2012 (Woo et al, 2012), infecting pig intestinal epithelia and causing severe diarrhea and vomiting (Ma et al, 2015). Several PDCoV strains were later detected in the United States (Alhamo et al, 2022), Canada (Ajayi et al, 2018), South Korea (Chung et al, 2017), Thailand (Janetanakit et al, 2016), China (Huang et al, 2020a), Japan (Suzuki et al, 2018), Vietnam (Le et al, 2018), etc., posing a severe threat to humans population associated with the swine industry. So far, all members of the delta CoV genus have been found in birds (Saeng-Chuto et al, 2017), implying that birds serve as the natural reservoir for these viruses (Jung et al, 2015;Ma et al, 2015).…”
Section: Epidemiology Of Covsmentioning
confidence: 99%
“…In early 2014, an outbreak of PDCoV-associated diarrhea broke out in pig farms in Ohio, United States, which led to the identification of the first clinical case of PDCoV infection in pigs [ 2 , 4 , 7 , 8 ]. Since then, PDCoV has been detected worldwide, including in Korea, Japan, China, Thailand, Vietnam, Laos, Peru, and Mexico [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. According to previous phylogenetic analyses, PDCoV can be divided into three or four groups based on their full-length genome sequences [ 15 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…KM820765) was first identified in April 2014 from the fecal samples of pigs with diarrhea [ 17 ]. Subsequent studies have shown that all Korean PDCoV strains identified during 2014–2016 have a high sequence identity with strains reported in the United States [ 10 , 18 , 21 ]. However, since 2016, there have been no reports of PDCoV outbreaks in Korea.…”
Section: Introductionmentioning
confidence: 99%